The influence of self-efficacy, social support, and psychological adjustment in undergraduate international students at a Public University In Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)

(untitled)
In Malaysia, international student enrolment is an important goal to the country’s higher education, the economy, and to the nation’s society in general. Since 2001, a flurry of newspaper and magazine articles has been published highlighting the decrease in the enrollment of international students in the United States after the events of September 11, 2001 (Alberts, 2007).